"Municipal settlements of Ukraine" database and its possible application spheres - Volodymyrovych, Glibchuk Petro (Bulletin of Geography. Socio-economic Series, 2016)
With the development of geoinformation technologies and geoinformation mapping the sphere of activity of professional geographers and cartographers has been enriched by a wide application of databases (DB). They enable geographical information to be put in order in a user-friendly system. The article considers the methodological aspects of the organizations and creation of such a system - the "Municipal settlements of Ukraine" databases. The basic stages and databases forming the principles which the author designated during the creation of this specific database are highlighted. The DB structure is revealed - the list of the data included in every table is given. The ways of DB applications are determined; they consist in using DB for the creation of various cartographic studies and reference books about the municipal settlements in Ukraine. The prospects of DB development and perfection are considered.